Arah Baru Pendidikan Islam Pasca Uu Pesantren - Suheri, Suheri; Nurrahmawati, Yeni Tri (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
The concept of Islamic education must be oriented to become a guide in developing the potential of faith in wading through the increasingly complex modernity of life. The existence of Islamic education in Law No. 4 of 1950 which has not been approved by the government so that nothing should be taken for religious studies in schools, then begins with